PENGARUH ATRIBUT, KUALITAS PELAYANAN, AKSESIBILITAS, DAN GETOK TULAR ELEKTRONIK TERHADAP KEPUASAN PENGUNJUNG TAMAN REKREASI MERAPI PARK - Fikri Farhan; Akromul Fajri; Guruh Ghifar Zalzalah; Adhi Prakosa (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The merapi park tourist attraction is one of the destinations that Indonesian tourists frequently visit. This research aims to examine the influence of attributes, service quality, accessibility, and electronic word of mouth on visitor satisfaction. The data collection method for this research used a questionnaire distributed through Google Forms. The sampling technique employed was purposive sampling, with a total of 283 respondents participating in the study. The data analysis technique used in this research was partial least squares structural equation modeling (PLS-SEM) utilizing SMART PLS version 4.0.9.6. The results of this study indicate that attributes, service quality, accessibility, and electronic word of mouth have a positive impact on visitor satisfaction